Tetrahydro-1,4-thiazine-3,5-dione - R. Alan Aitken; Alexandra M. Z. Slawin; Pei-pei Yeh (Molbank, 2018)
The X-ray structure of the title compound contains eight molecules in the unit cell which form the basis of a herringbone arrangement of hydrogen bonded ribbons.